QSAR Analysis of Amphipathic 3-Phenyl-7-propyl-benzisooxazoles as PPARγ, PPARδ and PPARαAgonist - Hemalatha, Rajaram; Manoj Kumar, Palanivelu; Chandra Mahajan, Suresh; Gopalrao Kaskhedikar, Sathish (Asian Journal of Chemistry, 2010)
A quantitative structural activity relationship (QSAR) study on a series of analogs of amphipathic 3-phenyl-7- propylbenzisooxazoles with agonist activity on PPARγ, PPARδ and PPARα has been performed using combination of various thermodynamic, electronic and spatial descriptors. Several regression expressions are obtained using multiple linear regression analysis. The best QSAR is further validated by leave-one-out cross validation method. The study reveals that thermodynamic parameters were found to have overall significant correlationship with PPARγ, PPARδ and PPARα agonist activity. Thus QSAR brings important structural insight to aid the design of potent new molecules.